Time spent outdoors through childhood and adolescence – assessed by 25‐hydroxyvitamin D concentration – and risk of myopia at 20 years. Issue 6 (10th January 2021) - Lingham, Gareth; Mackey, David A.; Zhu, Kun; Lucas, Robyn M.; Black, Lucinda J.; Oddy, Wendy H.; Holt, Patrick; Walsh, John P.; Sanfilippo, Paul G.; Chan She Ping‐Delfos, Wendy; Yazar, Seyhan
Abstract: Purpose: To investigate the relationship between time spent outdoors, at particular ages in childhood and adolescence, and myopia status in young adulthood using serum 25‐hydroxyvitamin D [25(OH)D] concentration as a biomarker of time spent outdoors. Methods: Participants of the Raine Study Generation 2 cohort had 25(OH)D concentrations measured at the 6‐, 14‐, 17‐ and 20‐year follow‐ups. Participants underwent cycloplegic autorefraction at age 20 years, and myopia was defined as a mean spherical equivalent −0.50 dioptres or more myopic. Logistic regression was used to analyse the association between risk of myopia at age 20 years and age‐specific 25(OH)D concentrations. Linear mixed‐effects models were used to analyse trajectory of 25(OH)D concentrations from 6 to 20 years. Results: After adjusting for sex, race, parental myopia, body mass index and studying status, myopia at 20 years was associated with lower 25(OH)D concentration at 20 years (per 10 nmol/L decrease, odds ratio (aOR)=1.10, 95% CI: 1.02, 1.18) and a low vitamin D status [25(OH)D < 50 nmol/L] at 17 years (aOR = 1.71, 95% CI: 1.06, 2.76) and 20 years (aOR = 1.71, 95% CI: 1.14, 2.56), compared to those without low vitamin D status. There were no associations between 25(OH)D at younger ages and myopia. Individuals who were myopic at 20 years had a 25(OH)D concentration trajectory that declined, relative to non‐myopic peers, with increasing age. Differences in 25(OH)D trajectory between individuals with and without myopia were greater among non‐Caucasians compared to Caucasians. Conclusions: Myopia in young adulthood was most strongly associated with recent 25(OH)D concentrations, a marker of time spent outdoors.